Peningkatan Prestasi Kerja Perawat Melalui Penyesuaian Gaya Kepemimpinan Transformasional, Lingkungan Kerja Dan Disiplin Kerja - Satryana, Hernita; Wekadigunawan, Wekadigunawan; Hasyim, Hasyim (Mandalika Institute, 2024)
Nurses' work performance is very important for the sustainability of the hospital. The problems faced by this hospital are lack of work discipline, low employee engagement and low work performance of nurses as seen from the assessment of individual key performance and this has an impact on hospital performance. The purpose of this study is to examine the hypothesized factors that can improve the work discipline of nurses which is expected to provide satisfaction to stakeholders in providing health services to hospital users. The results of this study are used by decision-makers to improve hospital management and hospital work performance. This research method uses a quantitative approach that is causal, namely the regression-Partial Least Square (PLS) method which shows the influence of independent variables on bound variables. The variables used are variables that are considered to be closely related to efforts to improve nurses' work performance, namely the variables of Transformational Leadership Style, Work Environment, and Work Discipline. Hypothesis testing is carried out through path analysis. The results of the study show that transformational leadership style affects work performance, work environment affects work performance, and work discipline affects work performance, both jointly and partially, This means that improvement in work performance can be done through adjustment of transformational leadership style, improvement of work environment and improvement of work discipline. The implications of the results of the study show that hospital management can improve work performance by improving the indicators of each variable. The findings of the study show that the Work Environment has the greatest influence on improving work performance.